A New Iterative Algorithm Based on Correction of Sensitivity Matrix for Electrical Resistance Tomography. (28th December 2019) - Chen, Yutong; Han, Yan; Yang, Wuqiang; Li, Kun
Abstract : Electrical resistance tomography (ERT) is used to reconstruct the resistance/conductivity distribution. Usually, a uniform distribution is assumed as the initial condition to obtain a generic sensitivity matrix, which may be very different from a theoretical sensitivity matrix, resulting in a large error. The aim of this study is to analyse the difference between a generalized sensitivity matrix and a theoretical sensitivity matrix and to improve image reconstruction. The effect of the generic sensitivity matrix and theoretical sensitivity matrix on image reconstruction is analyzed. The error caused by the use of the generic sensitivity matrix is estimated. To reduce the error, an improved iterative image reconstruction algorithm is proposed, which is based on calculation of the error between the generic sensitivity matrix and the theoretical sensitivity matrix, and a correction coefficient with a penalty. During the iterative process, the resistivity distribution and sensitivity matrix are alternatively corrected. Simulation and experimental results show that the proposed algorithm can improve the quality of images, e.g., of two-phase distributions.